Education-occupation mismatch among immigrants: evidence from the National Survey of College Graduates - Chen, Lieji (My University, 2025)
Using the National Survey of College Graduates, I examine the probability of immigrants being mismatched in their job with their education compared to native-born workers, and the earnings penalty experienced by mismatched immigrants versus mismatched natives. Male immigrants are less likely to be mismatched compared to male natives; however, controlling for education level and field of study explains most of the gap. Female immigrants are as likely to be mismatched as female natives, but controlling for various characteristics, female immigrants are slightly more likely to be mismatched than female natives. By looking at entry visas, immigrants who arrive as permanent residents are more likely to be mismatched than those who arrive on a temporary work visa. Immigrants face a larger earnings penalty from mismatch than natives due partly to immigrants tending to be in fields of study where mismatch is relatively costly.
Keywords: Immigrants; Education mismatch; Economics; Earnings penalty; Field of study